Short-term air pollution exposure and cardiovascular events: A 10-year study in the urban area of Como, Italy. (1st December 2017) - Vidale, Simone; Arnaboldi, Marco; Bosio, Vittorio; Corrado, Giovanni; Guidotti, Mario; Sterzi, Roberto; Campana, Carlo
Abstract: Background: In the last years several studies have investigated the effects of some air pollutants on cardiovascular diseases (CVD), but the results are not conclusive. Aim of this study was to investigate the association between short-term exposure to ambient air pollution and CVD events in a long-term observational period. Methods: All CVD events (myocardial infarction — MI and ischemic stroke — IS) which occurred in residents of Como between January 2005 and December 2014 were included. Demographics and main vascular risk factors were registered for each patient. Principal meteorological variables and four ambient particles (O3, SO2, NO2, PM10 ) were recorded. Statistical analysis was performed using linear regression (GLM) and a generalized additive model (GAM) estimating Poisson distribution and adjusted for the main risk factors and ambient meteorological variables. Results: A total of 4110 events were registered with a mild prevalence of MI (51.6%). In GLM analysis we observed a continuative association between CVD events and SO2 ( p  < 0.05), while PM10 was associated with CVD occurrences at two-day lag time ( p  < 0.05). Using GAM we observed a positive association between CVD and PM10 at the same day and at three- and four-day lag time with HRs ranging between 1.025 and 1.039 ( p  < 0.001). These results were observed for both MI and IS, with an earlier effect for MI than for IS. Conclusions: These data confirm a possible association between some ambient air pollutants and CVD events, precisely MI and IS, with different temporal and cumulative effect.